2016
DOI: 10.1038/srep37017
|View full text |Cite
|
Sign up to set email alerts
|

5-azacytidine affects TET2 and histone transcription and reshapes morphology of human skin fibroblasts

Abstract: Phenotype definition is controlled by epigenetic regulations that allow cells to acquire their differentiated state. The process is reversible and attractive for therapeutic intervention and for the reactivation of hypermethylated pluripotency genes that facilitate transition to a higher plasticity state. We report the results obtained in human fibroblasts exposed to the epigenetic modifier 5-azacytidine (5-aza-CR), which increases adult cell plasticity and facilitates phenotype change. Although many aspects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 47 publications
10
35
0
3
Order By: Relevance
“…Molecular analysis showed that PTFE encapsulated cells remained significantly hypomethylated for the entire length of the experiments. Furthermore, our results showed that epigenetic erasing led to an increased expression of the ten-eleven translocation family member TET2, accompanied by the onset of the pluripotency-related genes, OCT4, NANOG, REX1 and SOX2, as well as the up-regulation of EPCAM, and CDH1 genes, confirming and expanding previous studies carried out in our laboratory Manzoni et al, 2016;Pennarossa et al, 2014Pennarossa et al, , 2013. As we described above, this is the same mechanism taking place in epigenetic reprogramming which, in turn, replicates the methylation changes taking place during iPS reprogramming with the combined effect of reduced DNMT activity with the active demethylation controlled by TET proteins (Hysolli et al, 2016).…”
Section: Cell Spatial Arrangement In a 3d Microenvironmentsupporting
confidence: 91%
See 1 more Smart Citation
“…Molecular analysis showed that PTFE encapsulated cells remained significantly hypomethylated for the entire length of the experiments. Furthermore, our results showed that epigenetic erasing led to an increased expression of the ten-eleven translocation family member TET2, accompanied by the onset of the pluripotency-related genes, OCT4, NANOG, REX1 and SOX2, as well as the up-regulation of EPCAM, and CDH1 genes, confirming and expanding previous studies carried out in our laboratory Manzoni et al, 2016;Pennarossa et al, 2014Pennarossa et al, , 2013. As we described above, this is the same mechanism taking place in epigenetic reprogramming which, in turn, replicates the methylation changes taking place during iPS reprogramming with the combined effect of reduced DNMT activity with the active demethylation controlled by TET proteins (Hysolli et al, 2016).…”
Section: Cell Spatial Arrangement In a 3d Microenvironmentsupporting
confidence: 91%
“…Following on from the pioneering work of Taylor and Jones (1979), many groups have reported that it is possible to use small molecules and epigenetic modifiers in order to directly convert an adult cell into an alternative differentiated cell type Chandrakanthan et al, 2016;Manzoni et al, 2016;Pennarossa et al, 2013). Several protocols using epigenetic modifiers have been developed that can push cells to a transient 'less committed state', increasing cell plasticity for a short time, sufficient to redirect them towards a different cell type Chandrakanthan et al, 2016;Harris et al, 2011;Mirakhori et al, 2015;Pennarossa et al, 2014Pennarossa et al, , 2013.…”
Section: Epigenetic Cell Conversionmentioning
confidence: 99%
“…Moreover, our results suggest new context dependent combination approaches for the reactivating TET2, whereby either HAT inhibitors or sirtuin activators can be combined with AA. Other synergistic combinations, may also include hypomethylating agents azacytidine 51,52 and decitabine 53 , which has been reported to upregulate TET2 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…The thylcytosine dioxygenase TET2 could promote DNA demethylation to control the production of IFN-γ and IL-17 in autoimmunity [ 7 ], and was required to resolve inflammation by recruiting HDAC2 and repressing transcription of IL-6 through histone deacetylation [ 36 ]. A recent study also reported 5-azacytidine could induce the expression of TET2 and reshape morphology of human skin fibroblasts [ 37 ]. To our knowledge, this the first time to report that decitabine can control TET expression in CD4 + T cells and the importance of TET2 in controlling CD4 + T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%